Changes in the Serum Fatty Acid Profile After Anhepatic Phase of Orthotopic Liver Transplantation Procedure - Hliwa, Aleksandra; Mika, Adriana; Sledzinski, Maciej; Laski, Dariusz; Ramos-Molina, Bruno; Sledzinski, Tomasz (Frontiers in Physiology, 2022)
During orthotopic liver transplantation (OLT), the patients’ body remains deprived of this organ for some time, which could cause critical changes in the levels of various metabolites in the circulation, including fatty acids. Thus, the aim of this study was to determine whether the liver transplantation procedure leads to significant changes in the FA profile in serum lipids after the anhepatic phase. Our gas chromatography–mass spectrometry analysis revealed that after transplantation, serum levels of myristic and palmitic acids significantly decreased, whereas serum levels of very long-chain FAs containing 20 or more carbons in their chains were increased. These results indicate that the anhepatic phase during liver transplantation produces significant changes in serum fatty acid levels, and emphasizes the role of the liver in the metabolism of very long-chain fatty acids.